Sustainable development: through the implementation of green accounting and material flow cost accounting - Lubis, Irna Triannur; Aristantya, Selvi (Jurnal Mantik, 2024)
The background of this research is based on the importance of public awareness of environmental preservation. Currently, companies are required to carry out environmentally friendly business. Application of Green Accounting and Material Flow Cost Accounting to Sustainable Development, which includes four main aspects: economic, environmental, social and technological. Great attention to the imbalance between these aspects is the main focus of various parties. Currently, people will tend to use products from companies that implement green industry. Problems: An increase in the earth's average temperature can cause climate changes that are difficult to predict and extreme. The aim of the research is to analyze the effect of implementing green accounting, environmental performance and material flow cost accounting on the sustainable development of manufacturing companies on the Indonesian Stock Exchange. The population used in this research are companies listed on the Indonesia Stock Exchange 2021-2023. The sampling technique in this research used purposive sampling, so that a sample of 33 companies was obtained. The data used in this research is secondary data originating from the company's annual report. The analytical method used is multiple linear regression. It is hoped that the research results will be availableThe Effect of Implementing Green Accounting, Environmental Performance andMaterial Flow Cost Accounting for Sustainable Development of Manufacturing Companies on the Indonesian Stock Exchange